Automated and Continuous Production of Polymeric Nanoparticles - Bovone, Giovanni; Steiner, Fabian; Guzzi, Elia A.; Tibbitt, Mark W. (Frontiers in Bioengineering and Biotechnology, 2019)
Polymeric nanoparticles (NPs) are increasingly used as therapeutics, diagnostics, and building blocks in (bio)materials science. Current barriers to translation are limited control over NP physicochemical properties and robust scale-up of their production. Flow-based devices have emerged for controlled production of polymeric NPs, both for rapid formulation screening (~μg min−1) and on-scale production (~mg min−1). While flow-based devices have improved NP production compared to traditional batch processes, automated processes are desired for robust NP production at scale. Therefore, we engineered an automated coaxial jet mixer (CJM), which controlled the mixing of an organic stream containing block copolymer and an aqueous stream, for the continuous nanoprecipitation of polymeric NPs. The CJM was operated stably under computer control for up to 24 h and automated control over the flow conditions tuned poly(ethylene glycol)-block-polylactide (PEG5K-b-PLA20K) NP size between ≈56 nm and ≈79 nm. In addition, the automated CJM enabled production of NPs of similar size (Dh ≈ 50 nm) from chemically diverse block copolymers, PEG5K-b-PLA20K, PEG-block-poly(lactide-co-glycolide) (PEG5K-b-PLGA20K), and PEG-block-polycaprolactone (PEG5K-b-PCL20K), by tuning the flow conditions for each block copolymer. Further, the automated CJM was used to produce model nanotherapeutics in a reproducible manner without user intervention. Finally, NPs produced with the automated CJM were used to scale the formation of injectable polymer–nanoparticle (PNP) hydrogels, without modifying the mechanical properties of the PNP gel. In conclusion, the automated CJM enabled stable, tunable, and continuous production of polymeric NPs, which are needed for the scale-up and translation of this important class of biomaterials.